2020
DOI: 10.1016/j.algal.2020.101822
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical changes in Phaeodactylum tricornutum triggered by culture media: Implications for industrial exploitation

Abstract: Phaeodactylum tricornutum is a polymorphic marine diatom, displaying three main morphotypes: fusiform, triradiate and oval. It is of great interest for industrial biotechnology as a natural rich source of valuable eicosapentaenoic acid (EPA) and fucoxanthin. Changing culture conditions such as temperature and salinity has been shown to elicit morphological changes in P. tricornutum. However, limited information is available about the conditions that can be used for controlling cell morphology and growth of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
6
18
0
Order By: Relevance
“…Oval cells are able to release rapidly a higher amount of proteins, fusiform cells present a constant secretory activity at a mid-level while triradiate cells release progressively proteins over time from low-level to mid-level. Such results are complementary to recent findings published by Song et al (2020) that quantified higher protein content in oval cell cultures than in fusiform cell cultures for both Pt1 and Pt4 strains of P. tricornutum. In addition, as previously reported in Ovide et al (2018), RNA-Seq transcriptomic analysis performed on the three morphotypes of P. tricornutum Pt3 strain highlighted, in the oval morphotype, overexpression of genes encoding proteins involved in vesicular transports like the SAR1, a GTPase found in COP II vesicles; BET1 a Golgi vesicular transport from the ER to the Golgi complex; the SNARE SEC22 and the syntaxin 6, which displays important role in protein trafficking between the trans-Golgi network and the endosomal system.…”
Section: Comparison Of the Secretory Potential Of Pt3 Fusiform Oval And Triradiate Morphotypessupporting
confidence: 88%
See 2 more Smart Citations
“…Oval cells are able to release rapidly a higher amount of proteins, fusiform cells present a constant secretory activity at a mid-level while triradiate cells release progressively proteins over time from low-level to mid-level. Such results are complementary to recent findings published by Song et al (2020) that quantified higher protein content in oval cell cultures than in fusiform cell cultures for both Pt1 and Pt4 strains of P. tricornutum. In addition, as previously reported in Ovide et al (2018), RNA-Seq transcriptomic analysis performed on the three morphotypes of P. tricornutum Pt3 strain highlighted, in the oval morphotype, overexpression of genes encoding proteins involved in vesicular transports like the SAR1, a GTPase found in COP II vesicles; BET1 a Golgi vesicular transport from the ER to the Golgi complex; the SNARE SEC22 and the syntaxin 6, which displays important role in protein trafficking between the trans-Golgi network and the endosomal system.…”
Section: Comparison Of the Secretory Potential Of Pt3 Fusiform Oval And Triradiate Morphotypessupporting
confidence: 88%
“…In 2020, Song et al (2020) observed more and larger lipid bodies in Pt1 and Pt4 fusiform cells over time compared to oval cells. This implies higher neutral lipid accumulation in the fusiform cells from these P. tricornutum strains (Song et al, 2020).…”
Section: Localization Of Lipid Bodies In Pt3 Cellsmentioning
confidence: 83%
See 1 more Smart Citation
“…In fact, previous studies aiming to optimise the medium composition in order to increase EPS production highlight the role of sodium nitrate. It has been reported that increasing nitrogen concentration results in elevated EPS production (reviewed in [ 64 , 65 ]), although this is not consensual, and some authors have observed opposing effects [ 66 ]. Further studies need to be carried out in order to fully understand the intricate relationship between microalgae communities (including associated bacteria), nitrogen usage and response to challenging environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The algal cells from a 7-day old culture in BBM-Fe were washed and centrifuged at 2000× g for 3 min at RT. The cell pellets were resuspended in PBS buffer containing Dowex Marathon C (25g g -1 ) and gently mixed in a rotatory mixer (50 RPM) at 4°C for 1 h. Subsequently, the algal cells were centrifuged at 4000×g for 4 min, and the supernatant was subjected to overnight precipitation of exopolysaccharides in 70% ethanol (3:1 to supernatant) at 4°C [44]. Thereafter, the supernatant was centrifuged at 10,000×g for 10 min, and the pellet was collected for analyses by high-performance anion-exchange chromatography (HPAEC).…”
Section: Methodsmentioning
confidence: 99%